Design of an Auto-Tilting Car - Renjith Nimal, R.J. Golden; Sathyanarayanan, L.; Selvamani, T.; Siva, P.; Sriramprasanth, B. (International Journal of Psychosocial Rehabilitation, 2019)
In this I have tried to develop a tilting mechanism for a normal fuel run track car to give it the flexibility of a motor cycle. This feature enables the car to tilt in to the curve while negotiating it. Our analysis shows that to increase the maximum curve at speed by more than 50%. The method I have used is a simple mechanical tilting system controlled by a simple DC stepper motor which is controlled electronically. This tilting mechanism if successful should dramatically increase the maximum speed in curves. This should also provide the advantages of increased passenger comfort and handling. The idea is to develop a tilting car of normal fuel run track that seats two people in tandem. This can be operated on reduced lanes thereby increasing the effective capacity of highways.